High vacuum distillation for low-sulfur biodiesel production: From laboratory to large scale. (20th June 2019) - Xie, Qinglong; Cai, Li; Xia, Fan; Liang, Xiaojiang; Wu, Zhenyu; Liu, Yuanqing; Li, Xiaohua; Lu, Meizhen; Nie, Yong; Ji, Jianbing
Abstract: Desulfurization is important to the enhancement of biodiesel quality. In this study, the effects of reactant and catalyst addition and operations conducted on sulfur content at each stage during the biodiesel preparation process were examined. Based on the results of sulfide qualification and quantification, a high vacuum distillation method was developed to remove the sulfides in crude biodiesel. Biodiesel was separated into different fractions based on the boiling point and the sulfur content of each fraction was determined. Experimental results showed that most sulfides were distilled out with light and heavy fractions. Intermediate fraction was separated from the other fractions, resulting in high quality biodiesel with low sulfur content. The total yield of distillation fractions with sulfur content lower than 10 ppm reached 84.1%. A set of distillation facility with capacity of 10 m 3 /h was designed and developed accordingly for large-scale tests. The yield of low-sulfur biodiesel was around 83%, close to that obtained in the laboratory studies. In addition, economic analysis showed that the distillation facility can make revenue of more than $1.8 million per year, indicating that high vacuum distillation is economically feasible and promising for biodiesel desulfurization, especially in industrial application. Graphical abstract: Image 104946 Highlights: A high vacuum distillation method was proposed to remove sulfides in crude biodiesel. Sulfides in crude biodiesel were qualitatively and quantitatively analyzed. The total yield of biodiesel with sulfur content lower than 10 ppm was 84.1%. Distillation facility with capacity of 10 m 3 /h was developed for large-scale tests. The process is economically feasible for low-sulfur biodiesel production.